Remote temperature monitoring and controlling - Husin, Siti Huzaimah; Hassan, M Y N; Hashim, Nik Mohd Zarifie; Yusop, Yusmarnita; Salleh, Azahari (International Journal for Advance Research in Engineering and Technology, 2013)
This project is a stand-alone temperature and monitoring and control unit. It uses the remote control to adjust temperature in order to regulate the temperature. The system is also highly configurable in the setting up the features and parameters. The system consists of two units, the main control unit and the Radio Frequency (RF) remote control, with inputs to thermal sensors, and output to the Liquid Crystal Display (LCD). The RF remote control controls specific settings of the unit. The remote control is powered off a 9V battery. As the result, the developed system has been observed both from simulation and real circuit, and the test was considered successful. After the integration between hardware and software had been made, the circuit worked perfectly according to the value of temperature is working. For future improvement, there are several suggestions that are another sensor could be added to the system like alarm system and remote control also can be used e.g. Short Messaging System (SMS) would be